Engenharia de microestrutura de cerâmicas porosas - Vivaldini, Diogo Oliva (2013)
Refractory insulating is used to reduce thermal losses in industrial processes by decreasing the energy transfer rate between regions with distinct temperatures, therefore, increasing the energy efficiency of various industrial processes. Such efficiency optimization trend is not a recent phenomenon, instead, it has been intensified with the constant rise of the energy costs. The thermal insulation capacity of processes operating at high temperatures presents a direct correlation with energy costs, which can be reduced if the insulating performance is enhanced. The present work evaluated the refractory insulating microstructure effect on the material s thermal insulation capacity by indentifying their most suitable microstructural features. Moreover, the work aimed to select and analyze processing routes that could result the required microstructures by pointing out the main variables of ceramic foams generated by aqueous suspensions. Such foams must remain stable during the curing step, inhibiting the bubble coarsening. The liquid foams stability was studied in depth and theoretical models that aim to predict the geometrical and stability/foamability restrictions of the three-phase system (gas-liquid-particles) were generated. The thermal stability of porous microstructures was also analyzed, as they must also remain stable at high temperatures, without any significative porosity reduction and dimensional change of the body. In order to avoid these drawbacks, some routes to control the pore densification rate as a function of their sizes and of the grain boundaries chemical composition were evaluated. At last, this work led to a detailed and advanced knowledge of ceramic foams technology and suggested innovative ways to enhance the thermal insulation efficiency of such materials.